2016
DOI: 10.1016/j.smrv.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Has adult sleep duration declined over the last 50+ years?

Abstract: Summary The common assumption that population sleep duration has declined in the past few decades has not been supported by recent reviews, which have been limited to self-reported data. The aim of this review was to assess whether there has been a reduction in objectively recorded sleep duration over the last 50+ years. The literature was searched for studies published from 1960–2013, which assessed objective sleep duration (TST) in healthy normal-sleeping adults. The search found 168 studies that met inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 208 publications
(56 reference statements)
2
55
2
4
Order By: Relevance
“…In a review of data from 15 countries, sleep duration was reported to have increased in seven, decreased in six, and in two the results were mixed (Bin et al ., ). Other data suggest that sleep duration has stabilized or increased slightly over the past few decades, partially corroborating the GSS results (Bonke, ; Robinson and Michelson, ; Statistics Finland, ; Youngstedt et al ., ). Recent research focusing on sleep patterns in three preindustrial societies is also consistent with the GSS findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a review of data from 15 countries, sleep duration was reported to have increased in seven, decreased in six, and in two the results were mixed (Bin et al ., ). Other data suggest that sleep duration has stabilized or increased slightly over the past few decades, partially corroborating the GSS results (Bonke, ; Robinson and Michelson, ; Statistics Finland, ; Youngstedt et al ., ). Recent research focusing on sleep patterns in three preindustrial societies is also consistent with the GSS findings.…”
Section: Discussionmentioning
confidence: 97%
“…Reflecting a widespread perception that modern society imposes a ‘time crunch’, a common assertion is that substantial proportions of people today do not get enough sleep (Centers for Disease Control, ; Park, ; Robinson and Michelson, ). With few exceptions (Ford et al ., ; Keyes et al ., ), however, most of the research reported suggests that sleep duration has stabilized or increased slightly over the past few decades (Bin et al ., ; Bonke, ; Hoyos et al ., ; Robinson and Michelson, ; Statistics Finland, ; Youngstedt et al ., ). While methodological inconsistencies may account for some of the contradictory findings, the evidence to support the assumption of a sleep deficiency ‘epidemic’ is thus rather scarce.…”
Section: Introductionmentioning
confidence: 97%
“…Over the past century, the average duration of sleep of adults across the world has been declining . Inadequate sleep is known to be associated with several poor health outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Looking for modifiable factors associated with obesity that may be targeted in preventive interventions, the scientific research has addressed sleep duration, since parallel to the growth of obesity in Western societies there has been reported a systematic reduction of at least 1 h of the mean sleep duration in children and adolescents [2]. A modern epidemic of insufficient sleep has been, however, questioned in adults by several systematic reviews evidencing no significant decrements in self-reported and objective sleep duration over the last half-century [3,4]. For instance, Yougsteadt and colleagues [4], reviewing studies assessing objective-recorded sleep durations in healthy sleepers over the last half-century, evidenced a relative stability across years and age groups in both men and women, for both PSG and actigraphic data.…”
Section: Introductionmentioning
confidence: 99%
“…A modern epidemic of insufficient sleep has been, however, questioned in adults by several systematic reviews evidencing no significant decrements in self-reported and objective sleep duration over the last half-century [3,4]. For instance, Yougsteadt and colleagues [4], reviewing studies assessing objective-recorded sleep durations in healthy sleepers over the last half-century, evidenced a relative stability across years and age groups in both men and women, for both PSG and actigraphic data.…”
Section: Introductionmentioning
confidence: 99%